Atypical Moyamoya Disease Associated with Midaortic Syndrome - Bhargava, Nishant; Singh, Vivek; Sahu, Chandradev (Journal of Clinical Interventional Radiology ISVIR, 2021)
We report a case of a 4-year-old boy who presented with moyamoya disease associated with midaortic syndrome. He had been treated for severe persistent hypertension until he suffered multiple episodes of seizure and cerebral ischemic attack. Cerebral angiography showed bilateral terminal internal carotid artery stenosis. Angiographic survey showed severe stenosis of abdominal aorta and bilateral proximal renal arteries. This is a very rare report of moyamoya disease with midaortic syndrome.
Keywords: moyamoya; midaortic syndrome; abdominal aorta